2014
DOI: 10.5194/tc-8-1777-2014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing sea ice on the physical vulnerability of Arctic coasts

Abstract: Abstract. Sea ice limits the interaction of the land and ocean water in the Arctic winter and influences this interaction in the summer by governing the fetch. In many parts of the Arctic, the open-water season is increasing in duration and summertime sea-ice extents are decreasing. Sea ice provides a first-order control on the physical vulnerability of Arctic coasts to erosion, inundation, and damage to settlements and infrastructures by ocean water. We ask how the changing sea-ice cover has influenced coasta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 52 publications
6
107
0
Order By: Relevance
“…Much of the Chukchi and Beaufort seas' coastlines are similarly ice-rich and can be expected to be subject to the same mechanisms of geomorphologic change in response to shifts in environmental drivers of coastal dynamics (Ping et al, 2011). Regionally, relevant shifts in the energy and water balances at the land-atmosphere interface (Boike et al, 2013), increases in Lena River discharge (Fedorova et al, 2015) and increases in the duration of open water and coastal erosion (Günther et al, 2015) have recently been observed, matching similar circumpolar observations (Barnhart et al, 2014).…”
Section: Study Areasupporting
confidence: 64%
“…Much of the Chukchi and Beaufort seas' coastlines are similarly ice-rich and can be expected to be subject to the same mechanisms of geomorphologic change in response to shifts in environmental drivers of coastal dynamics (Ping et al, 2011). Regionally, relevant shifts in the energy and water balances at the land-atmosphere interface (Boike et al, 2013), increases in Lena River discharge (Fedorova et al, 2015) and increases in the duration of open water and coastal erosion (Günther et al, 2015) have recently been observed, matching similar circumpolar observations (Barnhart et al, 2014).…”
Section: Study Areasupporting
confidence: 64%
“…It is well documented that a lengthened period of open water leaves Arctic shorelines more vulnerable to erosion from fall storms (Barnhart et al, 2014;Overeem et al, 2011). Moreover, along the Alaskan coast during the open water period, we have found the number of wind events capable of doing geomorphological work or creating hazards to habitat or infrastructure (as defined by Atkinson, 2005) is increasing at all three communities in this study (Fig.…”
Section: Increasing Winds Over Open Water: Number Of Geomorphologicalmentioning
confidence: 55%
“…Over the 36-year time period examined, Kotzebue has had an approximate increase from 39 to 46.2 total wind events, while Shishmaref has seen an increase from an average of 49 to 52.6 events. In addition, wind direction is very important to determine whether a particular wind event is able to set up water along the coastline enough to cause flooding, increased coastal erosion, or infrastructure damage (Barnhart et al, 2014). The average number of high-wind events from the quadrant favorable for erosion at Utqiaġvik is approximately 4.61 with a significant increasing trend of 0.14 per year.…”
Section: Changes In Timing Of Freeze-up and Break-up And Number Of Famentioning
confidence: 99%
See 2 more Smart Citations